Effectiveness of golimumab in patients with ulcerative colitis: results of a real-life study in Switzerland. (February 2022) - Perrig, Kathrin; Krupka, Niklas; Jordi, Sebastian Bruno Ulrich; Rossel, Jean-Benoît; Biedermann, Luc; Greuter, Thomas; Schreiner, Philipp; Vavricka, Stephan R.; Juillerat, Pascal; Burri, Emanuel; Zimmermann, Dorothee; Maillard, Michel H.; et al.
Background: Tumor necrosis factor (TNF) inhibitors have improved treatment of ulcerative colitis (UC), but loss of response remains a frequent problem. The anti-TNF agent, golimumab, was approved in Switzerland for the treatment of UC in 2014. This study aims to summarize the experience of golimumab in a real-world setting in Switzerland. Methods: We analyzed real-world data from 1769 UC patients from the Swiss Inflammatory Bowel Disease Cohort (SIBDC) study and performed a chart review of golimumab-treated patients. We extracted the partial Mayo score at t0 (baseline), t1 (2–16 weeks), t2 (17–35 weeks), and t3 (36–89 weeks). The primary endpoint was clinical response at t1, defined as marked improvement in partial Mayo score and objective parameters. Clinical remission was defined as resolution of symptoms and normalization of objective parameters. Results: Our chart review included 103 UC patients with golimumab treatment (5.8% of all SIBDC UC patients); only 16 (15.5%) were anti-TNF naïve. Sixty-three patients remained on golimumab (61.2%) after 180 days, 51 (44.7%) after 365 days, and 34 (33%) after 630 days after the start of treatment. Upon golimumab treatment, the partial Mayo score decreased from 4 [interquartile range (IQR): 2–6] at t0 to 2 (IQR: 0–4) at t1, 1 (IQR: 0–3.5) at t2, and 1 (IQR: 0–3) at t3 ( p  < 0.001 for all comparisons with t0 ). The primary endpoint, clinical response at t1, could be evaluated in 52 patients and was met in 15 individuals (28.8%). Clinical remission at t1 was observed in 8 out of 52 patients (15.4%). Golimumab was generally well tolerated, one patient developed meningitis. The most frequent reasons to stop treatment were primary and secondary non-response. Conclusion: Golimumab was used in 5.8% of Swiss UC patients, mainly in biologic-experienced individuals. Golimumab treatment was associated with a sustained reduction of symptoms and clinical response in approximately 30% of patients. [ClinicalTrials.gov identifier: NCT00488631]